Compound heterozygous deletions in pseudoautosomal region 1 in an infant with mild manifestations of langer mesomelic dysplasia. Issue 2 (5th December 2013) - Tsuchiya, Takayoshi; Shibata, Minoru; Numabe, Hironao; Jinno, Tomoko; Nakabayashi, Kazuhiko; Nishimura, Gen; Nagai, Toshiro; Ogata, Tsutomu; Fukami, Maki
Abstract Haploinsufficiency of SHOX on the short arm pseudoautosomal region (PAR1) leads to Leri–Weill dyschondrosteosis (LWD), and nullizygosity of SHOX results in Langer mesomelic dysplasia (LMD). Molecular defects of LWD/LMD include various microdeletions in PAR1 that involve exons and/or the putative upstream or downstream enhancer regions of SHOX, as well as several intragenic mutations. Here, we report on a Japanese male infant with mild manifestations of LMD and hitherto unreported microdeletions in PAR1. Clinical analysis revealed mesomelic short stature with various radiological findings indicative of LMD. Molecular analyses identified compound heterozygous deletions, that is, a maternally inherited ∼46 kb deletion involving the upstream region and exons 1–5 of SHOX, and a paternally inherited ∼500 kb deletion started from a position ∼300 kb downstream from SHOX. In silico analysis revealed that the downstream deletion did not affect the known putative enhancer regions of SHOX, although it encompassed several non‐coding elements which were well conserved among various species with SHOX orthologs. These results provide the possibility of the presence of a novel enhancer for SHOX in the genomic region ∼300 to ∼800 kb downstream of the start codon. © 2013 Wiley Periodicals, Inc.